Evaluation of Cochlear Implant Receiver Position and Its Temporal Changes. Issue 10 (December 2017) - Grupe, Gloria; Rademacher, Grit; Hofmann, Solvig; Stratmann, Andreas; Mittmann, Philipp; Mutze, Sven; Ernst, Arneborg; Todt, Ingo
Abstract : Hypothesis: It was the aim of this study to establish normative data regarding intended changes in cochlear implants (CI) receiver positioning by one surgeon over time. Background: With the increasing number of CI patients, the probability of needing magnetic resonance imaging (MRI) increases. The accessibility of cerebral structures is limited by MRI artifacts caused by CI. New studies show a dependence of the visibility of intracranial structures by the MRI sequences and the position of the CI receiver itself. Methods: Retrospective and interindividual investigation of topograms with regard to the nasion–external auditory canal–internal magnet angle and the distance between the internal magnet and the external auditory canal. We evaluated scans of 150 CI recipients implanted from 2008 until 2015. Results: The most common implant position in the years 2008 to 2015 was a nasion–external auditory canal–internal magnet angle between 121 and 140 degrees (mean, 127 degrees) and an internal magnet–external auditory canal distance between 61 and 80 mm (mean, 70 mm). Over time the nasion–external auditory canal–internal magnet angle increased and the internal magnet–external auditory canal distance decreased, both to a statistically significant degree. A difference between the manufacturers was not observed. Conclusion: The CI receiver position is important for an artifact-free examination of the internal auditory canal and the cochlea. The realization of the position over a time course supports awareness of artifact-related visibility limitations.